Ten et Tru sur Bourbon Street - Liliane KERJAN (E-REA)
While Truman Capote was born in New Orleans (1924), the funeral bells toll for Tennessee Williams near Jackson Square and the Mississippi (1983). The crescent city is their favorite haunt and haven, a place of first times, the harbor of dreams. The two friends know their nest by heart, its balconies and bars, each celebrating love, freedom and Mardi-Gras. Williams sets short stories and such plays as A Streetcar Named Desire, Suddenly Last Summer, Vieux Carré in different parts of the city, whereas Truman Capote plays with the souvenirs of its secret angels and hidden gardens.New Orleans is their poem.